1995
DOI: 10.1002/jmv.1890470305
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal infection and persistence of human papillomavirus types 16 and 18 in infants

Abstract: Perinatal transmission of genital human papillomaviruses (HPVs), including HPV-16 and -18 which are associated with anogenital carcinomas have been described previously [Pakarian et al. (1994): British Journal of Obstetrics and Gynaecology 101:514-517; Kaye et al. (1994) Journal of Medical Virology 44:415-421]. A study was undertaken to investigate whether HPV-16 and -18 DNA in infants contaminated at delivery persists until they are 6 months of age. Of 61 pregnant women recruited, 42 (68.8%) were HPV-16 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
96
0
7

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 39 publications
4
96
0
7
Order By: Relevance
“…In humans and cows, papilloma virus is known to cause vertical infection, and PV infection of the fetus has been confirmed by PCR [1,12,15]. However, the present case was PV-negative on immunohistochemistry and PCR.…”
mentioning
confidence: 46%
“…In humans and cows, papilloma virus is known to cause vertical infection, and PV infection of the fetus has been confirmed by PCR [1,12,15]. However, the present case was PV-negative on immunohistochemistry and PCR.…”
mentioning
confidence: 46%
“…In two previous studies by Smith et al, only one mother/newborn pair was concordant for an HPV type, and among 203 infants, two had detectable HPV in oral or genital swabs (Smith et al, 1995(Smith et al, , 2004b. Studies on persistent HPV infection showed that the concordance between mother/newborn infections was maintained between 37% to 83% at six weeks to six months after birth (Cason et al, 1995;Fredericks et al, 1993;Kaye et al, 1996), whereas Rintala et al found that the prevalence declined to 10% in infants at 24 months of follow-up. This prospective cohort study assessed the dynamics of HPV transmission between parents and infants.…”
Section: Nonsexual Mode Of Transmissionmentioning
confidence: 99%
“…According to the age studied, there are variations in the prevalence rate. In nasopharyngeal aspirates collected immediately after birth, the detection rate of HPV varies from 1.5% to 37% (Cason et al, 1995;Castellsague et al, 2009;Mazzatenta et al, 1996;Puranen et al, 1996Puranen et al, , 1997Rintala et al, 2005aRintala et al, , 2005bRombaldi et al, 2008;Sedlacek et al, 1989;Tenti et al, 1997Tenti et al, , 1999Watts et al, 1998). At the age of 1-4 days, Smith et al in two studies found a low HPV incidence (from 0.9% to 1%) in the buccal swabs of neonates, whereas other studies showed a higher prevalence varying from 40% to 56% (Cason et al, 1995;Kaye et al, 1994;Pakarian et al, 1994;Tseng et al, 1998;Smith et al, 1995Smith et al, , 2004b.…”
Section: Incidence Of Hpv In Normal Oral Mucosamentioning
confidence: 99%
See 2 more Smart Citations